The Effect of Reporting of Exchange Rate Loses on the Stock Market Reaction - Grahita Chandrarin; Michael G. Tearney (The Indonesian Journal of Accounting Research, 2013)
In their seminal paper, Ball and Brown (1968) documented a positive statistical association between earnings surprises and stock returns around an earnings announcement. They concluded that earnings conveyed useful information to the market. However, the question of whether the exchange rate loss, as a component of earnings, affects the stock market has never been answered yet. The purpose of this paper is to examine the effect of reporting of exchange rate losses on the stock market. Empirical model is estimated using OLS and multiple regression is used to analyze the relationship between exchange rate loss and stock price.A sample of 106 companies is divided into group 1 (companies with exchange rate loss) and group 2 (companies without exchange rate loss). All of the data are derived from COMPUSTAT tape for the year 1995-1996, with Standard and Poor 500 category. The results of this study support the hypothesis that there is a correlation between reporting of exchange rate losses and stock price. Thus the stock price responds exchange rate loss reflexted in earnings.